Workshop Pembuatan Desain Label Kemasan sebagai Strategi Peningkatan Branding Produk Kuliner di Dusun Jlegong - Tyas, Maharani Ayuning; Cahyo, Ilham Dwi (Bengawan : Jurnal Pengabdian Masyarakat, 2025)
This community service activity aims to increase the capacity of culinary business actors in Jlegong Hamlet, Gemawang Village, Wonogiri Regency, in terms of understanding and skills in creating attractive, informative, and modern marketing standard product packaging label designs. The problem faced by local business actors is the lack of knowledge about the importance of packaging design as a means of promotion and product identity. The method of implementing this activity is in the form of an interactive workshop that includes the presentation of basic graphic design materials, direct practice using the Canva application, as well as consultation and evaluation sessions for participants' work. The results of the activity showed an increase in participants' understanding of the principles of good label design, as well as the ability to produce more professional packaging designs that are by the characteristics of local products. In addition, participants also showed high enthusiasm and a desire to further develop their products. This activity concludes that the packaging label design workshop can directly have a positive impact on improving the visual quality of local culinary products, which is ultimately expected to increase the competitiveness and selling value of products in a wider market.